2016
DOI: 10.1371/journal.pone.0164998
|View full text |Cite
|
Sign up to set email alerts
|

Quinoline Alkaloids Isolated from Choisya Aztec-Pearl and Their Contribution to the Overall Antinociceptive Activity of This Plant

Abstract: Choisya ‘Aztec-Pearl’, a hybrid of Choisya ternata and Choisya dumosa var. arizonica, had the antinociceptive activity in the ethanol extract (EECA) of its leaves evaluated. Two quinoline alkaloids, anhydroevoxine (A) and choisyine (C), isolated from these leaves were also tested. The results obtained pointed out to a very high antinociceptive activity measured by the hot plate model for EECA (at doses of 10, 30 and 100 mg/kg) as well as for A and C (at doses of 1, 3 and 10 mg/kg). The magnitude of the activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…arizonica, were investigated for antinociceptive activity. 210 At the doses of 3 and 10 mg/kg, these two N. Antinociceptive Activity furoquinoline alkaloids were twofold more potent than morphine in treated animals using the hot plate model. Furthermore, mechanistic studies indicated that the opiate and nitric oxide (NO) system may play an important role in the antinociceptive activity.…”
Section: Antinociceptive Activitymentioning
confidence: 94%
See 2 more Smart Citations
“…arizonica, were investigated for antinociceptive activity. 210 At the doses of 3 and 10 mg/kg, these two N. Antinociceptive Activity furoquinoline alkaloids were twofold more potent than morphine in treated animals using the hot plate model. Furthermore, mechanistic studies indicated that the opiate and nitric oxide (NO) system may play an important role in the antinociceptive activity.…”
Section: Antinociceptive Activitymentioning
confidence: 94%
“…Anhydroevoxine and choisyine ( 246 ) (Figure ) from Choisya Aztec‐Pearl, a hybrid of Choisya ternata and Choisya dumosa var. arizonica , were investigated for antinociceptive activity . At the doses of 3 and 10 mg/kg, these two furoquinoline alkaloids were twofold more potent than morphine in treated animals using the hot plate model.…”
Section: Biological Activities Of Quinoline and Quinazoline Alkaloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkaloids are generally toxic to man and many of them have shown physiological activities; hence they are widely used in medicine 13 . Quinolene alkaloid also reported in leaf extract of T. falciformis, previous studies on Quinolene reveals that it has antinociceptive 16 and antifungal activity 17 . Likewise, terpenoids are isoprene molecules that are significant not only in plant growth and ecology but also provide a shield against insects.…”
Section: Resultsmentioning
confidence: 81%
“…Hot plate test is a simple and extensively used method to investigate the central antinociceptive activity of drugs. 41 Both hot plate and tail flick models have been implicated, assessing the antinociceptive action of drugs in modulating acute thermal pain. However, the neurological mechanism of pain modulation is different in these models.…”
mentioning
confidence: 99%